Post-retrieval Extinction Prevents Reconsolidation of Methamphetamine Memory Traces and Subsequent Reinstatement of Methamphetamine Seeking - Chen, Ya-Yun; Zhang, Li-Bo; Li, Yue; Meng, Shi-Qiu; Gong, Yi-Miao; Lu, Lin; Xue, Yan-Xue; Shi, Jie (Frontiers in Molecular Neuroscience, 2019)
Methamphetamine abuse has become a serious public health problem. However, effective treatment for methamphetamine addiction still remains elusive, especially considering its high rate of relapse after treatment. A conditioned stimulus (CS) memory retrieval-extinction procedure has been demonstrated to decrease reinstatement of cocaine, heroin and alcohol seeking in rats, and to reduce cue-induced craving in heroin and nicotine addicts. The goal of the present study was to explore the effect of CS memory retrieval-extinction procedure on methamphetamine seeking in rats and the underlying mechanisms. We found that daily presenting extinction training within reconsolidation time window attenuated subsequent drug priming-induced reinstatement, spontaneous recovery, and renewal of methamphetamine seeking. We also found retrieval of methamphetamine-associated memories induced neuronal activation in basolateral amygdala (BLA), while presenting extinction within the time window of reconsolidation abolished the neuronal activation in BLA. These results indicated that the CS memory retrieval-extinction procedure could prevent reconsolidation of methamphetamine memory traces in BLA and subsequent methamphetamine craving and relapse.